Mating types, sexual reproduction and ploidy in fungi: Effects on virulence [Mantarlarda çaprazlaşma tipleri, eşeyli çoǧalma ve ploidinin virülans üzerine etkileri] - (:unkn) unknown (My University, 2009)
Sexual reproduction provides natural selection and adaptation of the organisms to environmental conditions by allowing benefical mutations to spread and by diluting deleterious mutations. In recent years new findings which indicate the role of sexual reproduction in fungal pathogenicity, have been obtained. However, the pathogenic fungi limit their sexual cycles to generate clonal populations instead of recombinants, to enable themselves to adapt to the new conditions in the environment and in the host such as antimicrobial therapy. Cryptococcus neoformans being a haploid organism has a laboratory diagnosed sexual cycle and mating cell types "a and α". Nutrient limitation stimulates production of pheromones that induce cell-cell fusion and the resulting dikaryon undergoes filamentous transition, karyogamy and meiosis in basidia and chains of very infective basidiospores develop. The "a" and "α" alleles take place in MAT (Mating Type) locus. Strains of "α" mating-type predominate in environment and clinical isolates and, in "a-α" coinfection model, α-cells exhibit more pathogenic behaviour than congenie "α" cells. In the most common pathogenic variety grubii, (serotype A) there is no difference in the virulence of cells of opposite mating types but, during co-infection α-cells more easily cross the blood-brain barrier. Additionally, α strains produce increased amounts of melanin and urease which enhance invasion of central nervous system. In C.neoformans a novel sexual cycle named as same-sex (monokaryotic) mating has been discovered, α-α cells engage in sex without an "a" partner that can contribute to generate diversity and produce infectious haploid basidiospores. This process is also called as "parasexual" recombination. Another aspect for C.neoformans biological property is naturally occuring AD hybrid strains between var. grubii (serotype A) and var. neoformans (serotype D) via sexual crosses. Those strains often contain both mating types, either aADα or αADa. In Candida albicans due to its diploid property, most strains are a/α heterozygous at the mating-type locus and contain both mating-type alleles. Thus, the tetraploid cells (a/a/α/α) generated during mating can turn to diploid state (a/a and α/α) by random chromosome loss via parasexual process but without meiosis, within the host. Tetraploids were found to be less virulent in murine infections and could be cleared more rapidly than the diploids. In C albicans, control of white-opaque switching Is believed to be regulated in part by the mating locus, suggesting switch may be involved in mating. Like these 2 opportunistic pathogens, in Pneumocystis jiroveci, Histoplasma capsulatum and Aspergillus spp. genetic studies are being carried out to identify genes related to mating types, sexual cycle, virulence and resistance to antifungal drugs, and the interactions between them.
Keywords: Fungi; Mating types; Sexual reproduction; Virulence